(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Artificial intelligence (AI) is rapidly transforming the workplace, and human resource management (HRM) practices need to adapt accordingly. This research paper will investigate the impact of AI on talent management strategies, including recruitment, selection, performance management, and employee development. It will explore how organizations can leverage AI to attract, develop, and retain top talent in the age of automation.